Anthropometric, cardiovascular and functional variables as indicators of health related physical fitness in university professors - Osvaldo Costa Moreira; Renata Aparecida Rodrigues de Oliveira; Cláudia Eliza Patrocínio de Oliveira; Leonice Aparecida Doimo; Paulo Roberto dos Santos Amorim; João Carlos Bouzas Marins
AbstractObjective To verify the behavior of anthropometric, cardiovascular and functional variables as indicators of health-related physical fitness in university professors and perform a comparison of these variables between sexes.Materials and methods We conducted an observational epidemiological cross-sectional study in 145 professors (45.86 ± 9.7 years), 103 men (71.03%), which were evaluated by measuring heart rate (HR) and systolic (SBP) and diastolic (DBP) pressure at rest, body weight, height, body mass index (BMI), body fat percentage (BF%), handgrip strength (HGS), flexibility and cardiorespiratory fitness (CRF). We proceeded to the descriptive analysis, Student t-test for comparison between sexes and multiple regression analysis to verify the association between the variables analyzed. It was adopted a significance level of p < 0.05.Results The sex affected all variables. Women had better levels of BMI, flexibility, SBP and DBP. The BF% and CRF were associated with SBP and BMI in both sexes.Conclusion The behavior of anthropometric, cardiovascular and functional variables indicated unsatisfactory values for flexibility, HGS and BMI, with the worst levels among men. Furthermore, the variables that showed better association with HRPF were BF% and CRF.